2006
DOI: 10.1002/pola.21799
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and photopolymerization of new dental monomers from o‐hydroxyaryl phosphonates

Abstract: Novel aromatic mono‐ and diphosphonate monomers based on t‐butyl α‐bromomethacrylate were prepared for use in dental composites. The synthesis of the two monomers involved three steps: the reaction of diethyl phosphite with phenol or hydroquinone, the rearrangement of the resulting phosphate derivatives into o‐hydroxyaryl phosphonates with lithium diisopropylamide, and the reaction of o‐hydroxyaryl phosphonates with t‐butyl α‐bromomethacrylate. Then, the selective hydrolysis of the t‐butyl ester groups of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 28 publications
0
31
0
Order By: Relevance
“…Previous studies reported that mixtures of acidic functional monomers with unmodified (di)methacrylates may exert a detrimental effect on both the rate and extent of copolymerization. 1,20,21 This event is explained by a deactivating effect of the acidic groups on freeradicals. Radicals terminated by an acid group are stable and hence less reactive than free-radicals derived from unmodified monomers, reducing the readiness with which the polymerization takes place.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported that mixtures of acidic functional monomers with unmodified (di)methacrylates may exert a detrimental effect on both the rate and extent of copolymerization. 1,20,21 This event is explained by a deactivating effect of the acidic groups on freeradicals. Radicals terminated by an acid group are stable and hence less reactive than free-radicals derived from unmodified monomers, reducing the readiness with which the polymerization takes place.…”
Section: Discussionmentioning
confidence: 99%
“…For example, kinetics of photopolymerization of phosphorus‐containing acrylate/(di)methacrylate monomers based on 3‐(acryloyloxy)‐2‐hydroxypropyl methacrylate (AHM) were investigated12 and led to a new family of phosphate‐containing cross‐linkers based on commercially available AHM potentially usable in applications in adhesives and flame retardant formulations where high local concentrations of active groups are necessary. Synthesis and photopolymerization of monomers from ortho‐ hydroxyarylphosphonates were also described in the literature 13. Aromatic mono‐ and di‐phosphonate monomers based on tert‐ butyl α ‐bromomethacrylate were prepared for use in dental composites 14.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, we synthesized phosphorus‐containing monomers based on alkyl α‐hydroxymethacrylates, methacryloyl chloride and glycidyl methacrylate via different routes to be used in dental materials 16–20. In this work, we report synthesis of new monomers based on alkyl α‐hydroxymethacrylates and AHM and containing aminophosphonate groups and investigation of their homopolymerization behavior using thermal or photopolymerization techniques to determine structure‐reactivity relationships of these monomers.…”
Section: Introductionmentioning
confidence: 99%